JOHN F. KENNEDY : A Life From Beginning to End (Hourly History, 2017)
John F. Kennedy is the president that everyone knows. He was a rich man’s son, an athlete, a war hero, a ladies’ man, an author, a president, his face rendered forever young because the last time Americans saw him, he was riding in a convertible in Dallas, his glamorous wife at his side. Then the bullets struck, and the assassinated president became a legend, the truth of his life obscured by his tragic and untimely death. But JFK had more depth to his character than the magazine covers indicated.